Association between Vitamin D Deficiency and Levels of Renin and Angiotensin in Essential Hypertension. (10th June 2022) - Han, Lu; Xu, Xin-Juan; Zhang, Jun-Shi; Liu, Hai-Ming
Abstract : Objective . The present study aims to investigate the relationship between vitamin D deficiency and renin-angiotensin-aldosterone levels in patients with essential hypertension. Methods . The present study observed two groups of patients from Urumqi, Xinjiang, China, from April 2017 to March 2018. There were two subject groups: the hypertension group (80 patients with essential hypertension selected by random cluster sampling) and the control group (76 healthy adults). The 25-hydroxyvitamin D (25(OH)D or vitamin D) levels were measured through electrolytes; fasting blood glucose, blood lipids, and other biochemical indicators were detected using immune chemiluminescence; and plasma renin activity and angiotensin II concentrations were detected with radio-immunity. Results . Comparison between the hypertension group and control group showed statistically significant differences in the systolic pressure and levels of 25(OH)D, renin, and triglycerides (P < 0.05 ). The correlation analysis showed that 25(OH)D was negatively correlated with renin ( r  = –0.185; P = 0.021 ) and positively correlated with systolic pressure ( r  = –0.105; P = 0.035 ). There were no statistically significant differences in diastolic pressure, fasting blood glucose, total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and triglycerides between the two groups. Conclusions . The results of the present study show that vitamin D deficiency is common in Urumqi, Xinjiang, China and vitamin D levels are negatively correlated with renin levels. Vitamin D plays an important role in regulating blood pressure by affecting renin levels through the renin-angiotensin-aldosterone system.